SNOWBALL THROWING: KETERAMPILAN PROSES DAN HSIL BELAJAR SISWA KELAS VIIIB SMP INSTITUT INDONESIA YOGYAKARTA - Maya Tri Wulandari (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The purpose of this research is to raise the interest and learning-result in Science for students in class VIII B through model a cooperative learning type Snowball Throwing. This type of research is a "Research The Act of The Class". The subject this research is the students in class VIIIB. while the object the activity t and its learning-result sciences. The data-collecting technique can be by the inquiry, test, observation, and documentation. The data analyzing calculated using analyzes technique, using percentage, qualitative descriptive and the indicator of success. The research result shows that the learning-activity and learning-result science has progressed every cycle.The result percentage the average activity indicator in cycle I am 56% and it increased up to 82% in cycle II. The students' Science learning-result average in pre-cycle also increased from 51,38 to 78,18 in cycle II. There are five students who succeed reaching the KKM in pre-cycle by the percentage 22,73%. Cycle I has 9 students with the percentage 40,91%. In cycle II, it increased there were 16 students with percentage 72,73%Â  succeed reaching the KKM.